Information Organization Activities in the Knowledge Management Setting- - Johnson Mulongo Masinde; Otuoma Sanya (Journal of Digital Information Management, 2021)
This study examines information organization activities in the knowledge management environment. The investigation commences with the long-drawn debate on the concept of Knowledge Management and the literature that has hitherto reviewed it. Furthermore, the study delves into how conventional bibliographic information retrieval techniques and expert search systems have heretofore been applied in the organization and retrieval of digital resources and if they can be employed in the Knowledge management setting. It is contended that though the procedures, tools, and techniques are effectual and productive, they cannot be utilized in a knowledge intensive environment. Accordingly, the study puts forth a generic knowledge management framework that can be applied in a knowledge management setting. In addition, it proposes novel research gaps in the context of information organization.